The Ambiguity of Punk Women ‘Masculinity’ in Kuehnert’s I Wanna Be Your Joey Ramone and Castellucci’s Beige Novel - Ellita Permata Widjayanti; Tarascania Audina; Andrian Santosa (Ethical Lingua: Journal of Language Teaching and Literature, 2020)
Punk constitutes a subculture that is perceived as an androgyny community in which there is no clear difference between men and women. However, this androgyny matter is questioned by the sexism that occurred through hegemonic masculinity. This study aims to see how the femininity of punk women intertwined with the hegemonic masculinity and to see the resistance to the hegemony in Kuehnert's I Want to Be Your Joey Ramone and Castellucci's Beige novel. The method used is descriptive analysis with the theory of hegemony masculinity. The results of this study indicate that hegemonic masculinity in punk is constructed through social structure and rock music. The resistance of women gets a rejection from both punk men and women themselves. The masculinity of punk women then raises the ambiguity of their position and role in the community.